Individual and county level predictors of asthma related emergency department visits among children on Medicaid: A multilevel approach. (2nd January 2017) - Baltrus, Peter; Xu, Junjun; Immergluck, Lilly; Gaglioti, Anne; Adesokan, Adeola; Rust, George
ABSTRACT: Objective : Disparities in asthma outcomes are well documented in the United States. Interventions to promote equity in asthma outcomes could target factors at the individual and community levels. The objective of this analysis was to understand the effect of individual (race, gender, age, and preventive inhaler use) and county-level factors (demographic, socioeconomic, health care, air-quality) on asthma emergency department (ED) visits among Medicaid-enrolled children. This was a retrospective cohort study of Medicaid-enrolled children with asthma in 29 states in 2009. Multilevel regression models of asthma ED visits were constructed utilizing individual-level variables (race, gender, age, and preventive inhaler use) from the Medicaid enrollment file and county-level variables reflecting population and health system characteristics from the Area Resource File (ARF). County-level measures of air quality were obtained from Environmental Protection Agency (EPA) data. Results : The primary modifiable risk factor at the individual level was found to be the ratio of long-term controller medications to total asthma medications. County-level factors accounted for roughly 6% of the variance in the asthma ED visit risk. Increasing county-level racial segregation (OR=1.04, 95% CI=1.01-1.08) was associated with increasing risk of asthma ED visits. Greater supply of pulmonary physicians at the county level (OR=0.81, 95% CI=0.68-0.97) was associated with a reduction in risk of asthma ED visits. Conclusions : At the patient care level, proper use of controller medications is the factor most amenable to intervention. There is also a societal imperative to address negative social determinants, such as residential segregation.